IMPLEMENTASI PERATURAN MENTERI KETENAGAKERJAAN NOMOR 2 TAHUN 2015 TERHADAP PERLINDUNGAN HAK PEKERJA RUMAH TANGGA DILINGKUNGAN KECAMATAN KRAMAT JATI - Munizar, Kasmedi; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2024)
The large number of workers in the scope of Domestic Workers should receive more attention. Domestic Workers should be included in formal sector workers who are protected by the provisions of the law. The living and working situations of domestic workers do not reflect workers at all. Domestic workers in carrying out their work are included in jobs that do not have legal norms like formal workers regulated in the UUK so that their rights as workers are neglected. There are no special regulations on domestic workers so that it is considered necessary to protect domestic workers and make regulations on the protection of domestic workers as the basis for Permenaker Number 2 of 2015 concerning the Protection of Domestic Workers. The research method uses normative legal research. The results of the study show that the government issued Permenaker No. 2 of 2015 concerning the Protection of Domestic Workers. But the regulation still has shortcomings. Minister of Manpower Regulation Number 2 of 2015 has included the rights of domestic workers in Article 7 and the obligations of domestic workers in Article 8. In addition, Article 5 of this regulation also stipulates that the parties must reach a written or verbal agreement, which reads